Methods for construction of socio-demographic profile of Internet users - Gomzin, A.; Kuznetsov, S. (Trudy Instituta sistemnogo programmirovaniâ, 2018)
The paper is devoted to methods for construction of socio-demographic profile of Internet users. Gender, age, political and religion views, region, relationship status are demographic attributes. This work is a survey of methods that detect demographic attributes from user’s profile and messages. The most of observed works are devoted to gender detection. Age, political views and region are also interested researches. The most of solutions are based on supervised machine learning. Each step of solution is observed in this work: data collection, feature extraction, feature selection, classifiers, evaluation of methods